Sensitivity of patients with familial cerebral cavernous malformations to therapeutic radiation. Issue 1 (7th January 2015) - Golden, Michael; Saeidi, Saba; Liem, Benny; Marchand, Eric; Morrison, Leslie; Hart, Blaine
Summary Familial cerebral cavernous malformations are autosomal dominant conditions that can result in significant morbidity. A two‐hit mechanism is accepted as likely responsible for formation of these malformations. We present two patients with this disease who received therapeutic radiation and developed very high numbers of malformations within the radiation ports, supporting radiation as an accelerator of lesion formation and suggesting implications for risks of radiation in this disease.